2018
DOI: 10.3390/ijms19051411
|View full text |Cite
|
Sign up to set email alerts
|

Mithramycin A Alleviates Osteoarthritic Cartilage Destruction by Inhibiting HIF-2α Expression

Abstract: Osteoarthritis (OA) is the most common and increasing joint disease worldwide. Current treatment for OA is limited to control of symptoms. The purpose of this study was to determine the effect of specificity protein 1 (SP1) inhibitor Mithramycin A (MitA) on chondrocyte catabolism and OA pathogenesis and to explore the underlying molecular mechanisms involving SP1 and other key factors that are critical for OA. Here, we show that MitA markedly inhibited expressions of matrix-degrading enzymes induced by pro-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The meniscus is a fibrocartilaginous tissue that extends mechanical integrity to the knee [ 45 ]. The loss of the meniscal function triggers increased mechanical stress in the articular cartilage, resulting in subchondral bone degeneration [ 46 ]. Furthermore, mechanical stress induces inflammatory responses in the articular cartilage via the secretion of IL-1β in the synovial region [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The meniscus is a fibrocartilaginous tissue that extends mechanical integrity to the knee [ 45 ]. The loss of the meniscal function triggers increased mechanical stress in the articular cartilage, resulting in subchondral bone degeneration [ 46 ]. Furthermore, mechanical stress induces inflammatory responses in the articular cartilage via the secretion of IL-1β in the synovial region [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several pharmacologic inhibitors have been shown to be effective in in vitro or in vivo OA models, with some executing their functions through NF-κB inhibition. The inhibitors reported have been developed against protein kinase Czeta (PKCzeta) [155,156], purinergic P2X7 receptor (P2X7R) [157], specificity protein 1 (SP1) [158], and receptor-interacting protein kinase 1 (RIPK1) [159]. Similar to the anti-catabolic effects of the pharmacologic PKCzeta inhibitor, inhibition of PKCzeta using molecular approaches, such as siRNA-mediated KD and the overexpression of dominant negative PKCzeta, also suppressed ECM degradation in inflammatory cytokine-treated chondrocytes [155,156].…”
Section: Chondrocyte Catabolism Regulated By Nf-κbmentioning
confidence: 99%
“…Similar to the anti-catabolic effects of the pharmacologic PKCzeta inhibitor, inhibition of PKCzeta using molecular approaches, such as siRNA-mediated KD and the overexpression of dominant negative PKCzeta, also suppressed ECM degradation in inflammatory cytokine-treated chondrocytes [155,156]. In contrast, the SP1 inhibitor mithramycin A showed anti-catabolic effects in chondrocytes by primarily suppressing the NF-κB-HIF2-α axis rather than by targeting SP1, as SP1 KD had minimal effects on catabolic gene expression in IL-1β-treated chondrocytes [158]. Collectively, these studies identified potential signaling pathways and targets for NF-κB inhibition.…”
Section: Chondrocyte Catabolism Regulated By Nf-κbmentioning
confidence: 99%
“…The experimental design of IA injection with peptide concentration and injection period is shown in each figure. For the experimental OA study, DMM surgery was performed as described previously [ 56 ]. Seven days after DMM surgery, the vehicle or Cramp peptide (10 μL of 25 μM; approximately 1 μg) was first injected into mice by IA injection, and then injected weekly a total of seven times before the mice were sacrificed at 9 weeks for histological analysis.…”
Section: Methodsmentioning
confidence: 99%